Rate of Legionella pneumophila colonization in hospital hot water network after time flow taps installation. Issue 1 (January 2018) - Totaro, M.; Valentini, P.; Costa, A.L.; Giorgi, S.; Casini, B.; Baggiani, A.
Summary: In hospital water systems legionellae may be resistant to disinfectants in pipework, which is a problem particularly in areas where there is low flow or stagnation of water. We evaluated legionella colonization of a water network of an Italian hospital after time flow taps (TFTs) installation in proximity to dead legs. The water volume flushed was 64 L/day from May 2016, and 192 L/day from December 2016. Before TFTs installation, Legionella pneumophila sg2-14 was detected in all points (4 × 10 4  ± 3.1 × 10 4  cfu/L). All sites remained positive (2.9 × 10 4  ± 1.9 × 10 4  cfu/L) through November 2016. From December 2016 legionella persisted in one point only (2 × 10 2 to 6.8 × 10 3  cfu/L). TFTs with chemical disinfection may reduce legionella colonization associated with dead legs.